Larch regeneration across an experimental burn severity gradient in far northeastern Siberia, 2013-2017 - Heather D. Alexander (Arctic Data Center, 2018)
Fire severity is increasing across the boreal forest biome as climate warms, and initial post-fire impacts on tree demographic processes could be an important determinant of long-term forest structure and carbon dynamics. To examine soil burn severity impacts on tree regeneration, we conducted experimental burns in summer 2012 that created a gradient of residual post-fire soil organic layer (SOL) depth within a mature, sparse-canopy Cajander larch (Larix cajanderi Mayr.) forest in the Eastern Siberian Arctic. Each fall from 2012 to 2016, we added larch seeds to plots along the burn severity gradient. We tracked density of new larch germinants and established seedlings (alive > 1 year) during subsequent growing seasons, along with changes in seedbed conditions (permafrost thaw depth, moisture, and temperature).